BK polyomavirus: a review of the virology, pathogenesis, clinical and laboratory features, and treatment. (August 2017) - Trang, Van Dinh; Rockett, Rebecca; Jeoffreys, Neisha; Trung, Nguyen Vu; Hai An, Ha Phan; Kok, Jen; Dwyer, Dominic E
BK polyomavirus (BKPyV) is a non-enveloped, circular dsDNA virus with a genome of approximately 5100 base pairs. It can be divided into four major genotypes, but the effects of different genotypes on clinical disease are uncertain. Primary BKPyV infection is generally acquired asymptomatically in childhood. It establishes low-level persistence in many tissues, particularly the genitourinary tract. Reactivation can lead to severe disease including BKPyV-associated nephropathy confirmed by renal biopsy, hemorrhagic cystitis and meningoencephalitis. Nucleic acid amplification testing of blood and urine is the main diagnostic and prognostic test for BKPyV infection. The treatment of BKPyV infection has concentrated on reduction in immunosuppressive therapy. Recent studies suggest that antiviral drugs have demonstrated only modest benefit, but adoptive T-cell therapies offer potential advances.